O riso erótico em discursos burlescos de Antônio da Fonseca Soares - Lopes, André da Costa (2019)
In this thesis, we study authorality in Antônio da Fonseca Soares’ burlesque discursive production, a central figure in the literary-linguistic production of the seventeenth century in Portugal. The theoretical-methodological framework of French Discourse Analysis, mainly the enunciative-discursive approach proposed by Maingueneau, conducts this research. We investigate the authorship in the Baroque literary discourse starting from a question related to authorial responsibility in this period and considering the possibility of the Discourse Analysis contributing to elucidate the manifestation of authorality in the socio-historical-cultural production conditions of this discourse. In view of this, we aim to examine the procedures of authorship and the author’s enunciative position in the Antônio da Fonseca Soares’ burlesque discourse. The corpus of this research, therefore, is constituted by a set of one hundred and thirty-four romances, a genre of literary discourse configured linguistically as a narrative poem. These romances are compiled in the manuscript 2998, filed in the Reserved Room of the General Library of the Coimbra University and in the textual criticism work developed by Maldonado (1992). Through this set of texts, we map the authorship norms of what we understand in this thesis as a burlesque discursive formation. From there, we describe the process of authorality in this specific area of seventeenth-century literary discourse. In the course of the analysis, the results show that, even in an authorial system centered on the imitation aesthetic, the dynamics of authorship do not go away. The name Antônio da Fonseca Soares highlights the need to associate an authorial instance with a set of discourses and a trajectory in the literary field. In the text, the framing and the play with the authorship norms reveal authorial gestures, from which emerges a creative force, recognized by Baroque reception as a model author, an auctor